PERLINDUNGAN DUTA BESAR ITALIA OLEH REPUBLIK DEMOKRATIK KONGO DITINJAU DARI HUKUM DIPLOMATIK - Angela Farrah Azizah; Maya Indrasti Notoprayitno (Reformasi Hukum Trisakti, 2022)
The ambassador is in charge of the diplomatic mission that is under international protection. The diplomat is granted immunity and perks to speed up the mission he will carry out. The killing of the Italian ambassador in the Democratic Republic of the Congo in 2021 highlights the question of how the sending country's efforts to hold this case accountable and the receiving country's measures to protect diplomatic staff. This research is normative in nature and was based on literature reviews. It was qualitatively examined using deductive approaches and secondary data collecting. The analysis' findings, which are based on the 1961 Vienna Convention and the 2001 ILC State Accountability Draft, indicate that the DRC failed in carrying out its obligations to protect and guarantee the safety of the Italian ambassador. RDK should be able to take more action than just carry out satisfaction accountability. Therefore, it was concluded that Italy has the right to hold internationally responsible for the DRC's failure to protect diplomatic officials.